HUBUNGAN ANTARA KECEMASAN DENGAN KETEPATAN FLOATING OVERHAND SERVE BOLAVOLI PADA SISWA EKSTRAKULIKULER BOLAVOLI DI MA NEGERI RENGEL KABUPATEN TUBAN - MUH.HASAN FAHMI (Universitas Negeri Surabaya, 2013)
ABSTRACT The main purpose of this research was to examine the correlation between enxiety and precision floating overhand serve in volleyball extracurricular student at MA at MA Negeri Rengel. this research is consist of one one independent variable and one dependent variable, which are : a) anxiety and b) precision floating overhand serve. The type of this research is correlational research. Subject of this research are students extracurricular volleyball at MA State Rengel. The number of this research subject is 21 students. Data analytical technique used in this research is